#### Answer

$3$

#### Work Step by Step

$=\frac{f(a+h)-f(a)}{h}$
Use $f(x)=3x+7$ in the given function.
$=\frac{3(a+h)+7-(3a+7)}{h}$
$=\frac{3a+3h+7-3a-7}{h}$
$=\frac{3h}{h}$
$=3$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.